SYNTHESIS OF SOME NEW PYRIMIDINE DERIVATIVES INCORPORATED INTO OTHER HETEROCYCLES FOR BIOLOGICAL EVALUATION (Biological Sciences - PJSIR, 2002)
Chloroacetyl pyrimidine was synthesized and reacted  with  both  aromatic  amines  and  hydrazine  hydrate.  Hydrazide was reacted with !3-dicarbonyl compounds and also with different acid anhydrides. 2-Amino-pyrimidine afforded new Schiff 's bases which were cyclized with thioglycolic acid and thiolactic acid . Thiosemicarbazido derivatives  were cyclized to give thiadiazole which gave Mannich bases. Some of the  newly  prepared  compounds  were  biologically tested  as antimicrobials